'A milder type of bondage': Brazilian slavery and race relations in the eyes of American abolitionists, 1812–1888. (2nd January 2018) - Skidmore, William E.
ABSTRACT: This article examines how American abolitionists educated themselves about Brazilian slavery and race relations. Beginning with the Iberian–American Revolutions and ending with James Redpath's 1867 influential exposé on Brazil, this article explores how American abolitionists viewed Brazil and how their understandings about Brazilian slavery and race relations changed over the course of the nineteenth century. These changes were not a progressive march by abolitionists toward a deeper and better understanding of Brazil but, instead, reflect how antislavery writers emphasized various aspects of Brazilian slavery and culture at different periods in order to further their own ideological and political agendas. At the same time, these agendas led abolitionists to pioneer some of the earliest methods for the comparative study of slavery on a global scale.